2009
DOI: 10.1097/coc.0b013e318178e513
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial of Weekly Topotecan and Gemcitabine in Patients With Solid Tumors

Abstract: Objective This phase I trial was designed to determine the maximal tolerated dose (MTD) of the combination of topotecan and gemcitabine given in a weekly schedule. Materials and Methods In this single-arm, open label, dose-escalation study, we administered topotecan (0.75–1.5 mg/m2) and gemcitabine (1000 mg/m2) on days 1, 8, and 15 every 4 weeks to 25 patients with advanced solid tumors. Results The topotecan MTD, when combined with gemcitabine, was 1.25 mg/m2/wk. Dose-limiting toxicities consisted of febr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, this causes the formation of irreversible double-stranded DNA breaks when a DNA replication fork collides with the cleavable complex 5 , 6 , Camptothecins can show preferential or selective toxicity to proliferating cells, particularly tumor cells, which are highly proliferative. As a result, the camptothecin analogs topotecan and irinotecan have already been widely used to treat several solid tumors, including colorectal carcinoma 7 , 8 and lung cancer 9 12 . Recently, irinotecan has also shown promising results for the treatment of advanced ESCC 13 15 .…”
Section: Introductionmentioning
confidence: 99%
“…However, this causes the formation of irreversible double-stranded DNA breaks when a DNA replication fork collides with the cleavable complex 5 , 6 , Camptothecins can show preferential or selective toxicity to proliferating cells, particularly tumor cells, which are highly proliferative. As a result, the camptothecin analogs topotecan and irinotecan have already been widely used to treat several solid tumors, including colorectal carcinoma 7 , 8 and lung cancer 9 12 . Recently, irinotecan has also shown promising results for the treatment of advanced ESCC 13 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies utilizing different doses and schedules of gemcitabine and topotecan have shown variable activity in numerous solid tumors [25][26][27][28]. Particular activity has been suggested in non-small cell lung [25,26] and head and neck carcinomas [28].…”
Section: Discussionmentioning
confidence: 98%